Development of Augmented Reality Based Simulation Media For Computer And Network Engineering Competency in Vocational High Schools - Riska, Muhammad; Syahrul; Mappalotteng, Abdul Muis (PT Maju Malaqbi Makkarana, 2025)
This study aimed to develop and evaluate Augmented Reality (AR)-based simulation media to enhance the Computer and Network Engineering (TKJ) competency in Vocational High Schools (SMK). Employing a Research and Development (R&D) approach, the product was designed as an Android application that integrates interactive 3D models of networking devices, marker-based visualization, and guided configuration tutorials. The development process included needs analysis, design, systematic development, implementation, evaluation, and revision stages. Participants were TKJ teachers and Grade XI students from three SMKs in South Sulawesi, Indonesia. Data were collected through interviews, questionnaires, expert validation, and pre-test/post-test assessments. The results showed a validity score of 98.14% (very valid), practicality score of 97.09% (very practical), and effectiveness with an N-Gain of 0.97 (high). User responses recorded 85.88% positive feedback, indicating high engagement and perceived usefulness. The findings demonstrate that AR simulation media can effectively bridge the gap between theoretical instruction and practical skill development, especially in schools with limited physical resources. Its portability, ease of use, and alignment with vocational learning principles make it a promising solution for improving instructional quality and supporting the revitalization of vocational education.